A Remnant Preservation Technique for All-Inside Anterior Cruciate Ligament Reconstruction - Yizhong Peng, M.D.; Wenbo Yang, Ph.D.; Wei Yu, Ph.D.; Chunqing Meng, Ph.D.; Hong Wang, Ph.D.; Wei Huang, Ph.D. (Arthroscopy Techniques)
Most knee sports injuries involving the anterior cruciate ligament (ACL) are proximal ACL tears. The all-inside ACL reconstruction technique has drawn great attention, aiming to minimize tissue disruption while restoring ACL function. Arthroscopic ACL remnant preservation has shown great potential in repairing ACL anatomic and biological function by facilitating the revascularization and reinnervation of implanted grafts. Although many techniques for ACL remnant preservation have been developed, preserving the integrity of the ACL remnant in all-inside ACL reconstruction is still challenging. To further improve operational convenience and reliability, we have developed a remnant preservation technique for all-inside ACL reconstruction. This technique uses preset sutures on the ACL remnant, with an longitudinal incision on the anterolateral side of the ACL remnant, along with an auxiliary anteromedial portal, to better reveal the tibial footprint area while preserving the integrity of the ACL remnant. The preset sutures also allow for the fixation of the remnant on a femoral cortical button through our all-inside ACL reconstruction technique. This technique offers the benefits of being both economical and safe for preserving the ACL remnant, as well as being convenient for securing the remnant to the bone cortex, with the goal of facilitating the repair of proximal ACL tears.